Study of the Deformation/Interaction Model: How Interactions Increase the Reaction Barrier - Zhiling Liang; Houhe Liu; Nianjun Su; Dandan Song; Yun Zhang; Hong Huang; Jianqi Zheng; Cheng Zhong; Guodong Ye (Journal of Chemistry)
The interactions (including weak interactions) between dienophiles and dienes play an important role in the Diels-Alder reaction. To elucidate the influence of these interactions on the reactivity, a popular DFT functional and a variational DFT functional corrected with dispersion terms are used to investigate different substituent groups incorporated on the dienophiles and dienes. The bond order is used to track the trajectory of the cycloaddition reaction. The deformation/interaction model is used to obtain the interaction energy from the reactant complex to the inflection point until reaching the saddle point. The interaction energy initially increases with a decrease in the interatomic distance, reaching a maximum value, but then decreases when the dienophiles and dienes come closer. Reduced density gradient and chemical energy component analysis are used to analyse the interaction. Traditional transition state theory and variational transition state theory are used to obtain the reaction rates. The influence of tunneling on the reaction rate is also discussed.